THE STRATEGY OF MANAGEMENT SYSTEM STANDARDS: A VARIANCE-BASED STRUCTURAL EQUATION MODELING (VB-SEM) - Md. Mamun Mia, Mohammed Masum Iqbal (International Journal of Advanced Science and Technology, 2020)
This study discovers the procedures of variance-based in structural equation modeling as management system standards on business sustainability. The aim is to discover whether the management system standards strategy helps to develop sustainable business goodwill indirectly with the moderating effect of implementation. The study applied a quantitative method. The source of data gathering is questionnaires surveyed from ready-made-garment manufacturers in Bangladesh by a cluster sampling technique. The development of a hypothesis-testing conceptual framework of the management system standards model shows the mediating role of sustainable business suggesting the significance of sustainable business goodwill. The output shows that strategy of management system standards helps to improve the sustainability of company business goodwill by strategies of management system standards traits of quality, environmental, and occupational health and safety standards in the form of indirect mediation with moderating effect. It exposes that the mediating and moderating roles of sustainable business and implementation which helps to increase business goodwill through a new variable of moderating effect attention harmonized towards sustainable business goodwill statistically significant.